How to make anything gluten free : over 100 recipes for everything from home comforts to fakeaways, cakes to dessert, brunch to bread - Excell, Becky (Quadrille, an imprint of Hardie Grant Publishing, 2021)
Are you avoiding gluten but yearn for fresh bread, all your favourite takeaways or a naan bread with your curry? And for your sweet tooth do you crave jam doughnuts, bakery-style cookies and classic cakes? How to Make Anything Gluten-Free is the first cookbook that shows you how to unlock all the food you truly miss eating - but nothing tastes or looks gluten-free . Becky Excell has spent years developing delicious dishes and sharing them with her followers on Instagram. She is here to show you that a gluten-free life can be exciting and easy, without having to miss out on your favourite foods ever again. Why restrict yourself to the obvious soups, salads and fruit? What you really want are the recipes that you think you can't eat! From proper chicken chow mein to pad thai, doughnuts to lemon drizzle cake, cheesecake to profiteroles, French baguettes to pizza, plus dairy-free, vegan, veggie and low FODMAP options, Becky gives you all the recipes you'll ever need with tips and advice on how to make absolutely anything gluten-free.